Pengaruh Brand Image Kualitas Produk dan Gaya Hidup Terhadap Keputusan Pembalian Iphone - Didid Pujianto (Yayasan Jompa Research and Development, 2022)
This study aims to determine how brand image, product quality, and lifestyle influence the public's iPhone purchase decisions. This study used quantitative methods with a total population of 60 respondents, namely people who use the iPhone. This research is limited only to people who like to wear branded goods. sampling using a purposive sampling technique using SPSS Version 22. The sampling refers to Roscoe (1975). using a sample size of > 30 respondents and 500 respondents. So for this study, the minimum number taken was 60 respondents. Primary data is employed, and questionnaires are used as a data gathering tool. The validity and reliability requirements were satisfied by the data utilized. According to the findings of hypothesis testing, brand image (X1), product quality (X2), and lifestyle (Y) all significantly influence consumers' decisions to buy iPhones in Sampit City.